2021
DOI: 10.1101/2021.05.25.445490
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Biomechanical property of limbal niche maintains stemness through YAP

Abstract: Stem cells (SCs) decision to self-renew or differentiate largely depends on the extracellular environment and elasticity of their niche. A well-described mediator of the mechanotransduction pathway is the co-transcriptional activator Yes-associated protein (YAP), known to shuttle into the nucleus of cells grown on stiff matrices. YAP is also known to be essential for stemness, but confusingly, SCs often reside in soft niches. Furthermore, the role of matrix rigidity in niche formation and SC function in vivo i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 95 publications
(199 reference statements)
0
4
0
Order By: Relevance
“…During the submission of our manuscript, Bhattacharya et al reported that the activity of YAP played significant roles in maintaining LESCs via the mechanotransduction pathway, and the inhibition of YAP by VTP hindered the de-differentiation of CECs in vivo (48). However, we observed rare nuclear YAP in LESCs during normal homeostasis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…During the submission of our manuscript, Bhattacharya et al reported that the activity of YAP played significant roles in maintaining LESCs via the mechanotransduction pathway, and the inhibition of YAP by VTP hindered the de-differentiation of CECs in vivo (48). However, we observed rare nuclear YAP in LESCs during normal homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…As for the opposing effects of VTP on the de-differentiation of CECs, we surmise that might result from these different markers used to identify LESCs. Bhattacharya et al used CK15-GFP, CD63 and IFITM3 to mark LESCs (48). However, we found that CD63 and IFITM3 were also expressed by basal cells of peripheral and central epithelium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, clinical tumors are highly heterogeneous. Extending this work to include three ( 56 ) or more types will allow us to better model more clinically relevant resistance evolution. Last, our results suggest that ecological effects are an important consideration in competition experiments, and continuing to show this empirically remains a priority going forward.…”
Section: Discussionmentioning
confidence: 99%